A probe into the deeper structure of the Saldania Belt: pressure-temperature-time signatures of Malmesbury group xenoliths hosted in the Darling Batholith - Cilliers, Kirstin (Stellenbosch : Stellenbosch University, 2019)
Thesis (MSc)--Stellenbosch University, 2019.